Advances in design, simulation and manufacturing : proceedings of the International Conference on Design, Simulation, Manufacturing: The Innovation Exchange, DSMIE-2018, June 12-15, 2018, Sumy, Ukraine /: proceedings of the International Conference on Design, Simulation, Manufacturing: The Innovation Exchange, DSMIE-2018, June 12-15, 2018, Sumy, Ukraine. ([2019]) - Unknown
No abstract available